The strategic use of translingual resources in Inner Circle academic settings. Issue 2 (16th March 2020) - Rincon‐Mendoza, Lupe; Canagarajah, Suresh
Abstract: Standardized American English is treated as normative for US academic interactions. However, international scholars use translingual practices effectively to negotiate academic relationships and practices. In a sequential analysis of research group meetings (RGMs),  we show the importance of spatial repertoires in stance negotiations to understand how normative English is renegotiated in Science, Technology, Engineering, and Math (STEM) mentoring interactions. The strategic use of spatial repertoires by an international scholar demonstrates the competence he brings for effective stancetaking in academic communication, belying his classification as lacking proficiency in academic English. Our findings highlight the deft negotiations of power through the scholar's orientations towards verbal and semiotic resources in interpersonal stances. We show that regardless of institutional hierarchies, positions taken by senior and novice scholars reflect the fluidity in knowledge and expertise in STEM. The use of spatial repertoires mediates the negotiation of these relationships and language norms.